2007
DOI: 10.1105/tpc.106.045666
|View full text |Cite
|
Sign up to set email alerts
|

INCREASED SIZE EXCLUSION LIMIT2Encodes a Putative DEVH Box RNA Helicase Involved in Plasmodesmata Function duringArabidopsisEmbryogenesis

Abstract: Here, we characterize the Arabidopsis thaliana embryo-defective mutant increased size exclusion limit2 (ise2). In contrast with wild-type embryos, ise2 mutants continue to traffic 10-kD fluorescent dextran in the mid-torpedo stage of development. ise2 embryos contain branched as well as simple plasmodesmata (PD) compared with wild-type embryos, which only contain simple PD. Positional cloning reveals that the ISE2 gene encodes a putative DEVH box RNA helicase that shares sequence homology with RNA helicases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
112
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 61 publications
2
112
0
3
Order By: Relevance
“…All five of these mutants produce severe phenotypes during embryo or seedling development; however, except GSL8 none encodes proteins that localize to PD. ISE1 encodes a mitochondrial DEAD-box RNA helicase (22), ISE2 encodes a chloroplast DEVH-type RNA helicase (23,30), GAT1 encodes a chloroplast thioredoxin (26), and DSE1 encodes a WDR protein that localizes to the nucleus and cytoplasm. Only, GSL8 encodes a putative glucan synthase, that may localize close to PD, as it is involved in callose deposition in cell walls at the cell plate (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All five of these mutants produce severe phenotypes during embryo or seedling development; however, except GSL8 none encodes proteins that localize to PD. ISE1 encodes a mitochondrial DEAD-box RNA helicase (22), ISE2 encodes a chloroplast DEVH-type RNA helicase (23,30), GAT1 encodes a chloroplast thioredoxin (26), and DSE1 encodes a WDR protein that localizes to the nucleus and cytoplasm. Only, GSL8 encodes a putative glucan synthase, that may localize close to PD, as it is involved in callose deposition in cell walls at the cell plate (31).…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of PD aperture in embryo development occurs at the midtorpedo stage (21). This transition in embryonic PD aperture provided the basis for a genetic screen that identified two mutants, increased size exclusion limit1 (ise1) and ise2, that fail to down-regulate PD permeability (22,23). These mutants also have increased proportions of branched (X-and Y-shaped) PD and twinned PD (15).…”
mentioning
confidence: 99%
“…Despite the fact that there are at least 58 DEAD-box helicases present in the Arabidopsis genome (Mingam et al, 2004), apparently none shared sufficient redundancy with PRH75 given the lethality of the prh75 mutation. There have been 800 emb genes identified to date in this model plant, of which seven were D/RNA helicases (At1G01040, At1G08840, At1G12770, At1G20960, At1G32490, At3G53110, and At5G26742) (Tzafrir et al, 2004), and an additional four D/RNA helicases, other than PRH75, have since been identified as belonging to the emb category (At1G70070 [Kobayashi et al, 2007], At2G35340 [Pagnussat et al, 2005], At5G08610 [PIGMENT DEFECTIVE 340…”
Section: Prh75 Is An Essential Enzyme For the Arabidopsis Life Cyclementioning
confidence: 99%
“…We have mapped and cloned two genes, INCREASED SIZE EXCLU-SION LIMIT (ISE)1 and ISE2, that, when mutated, result in increased intercellular transport of fluorescent 10-kDa dextrans at the midtorpedo stage of embryogenesis. In addition to increased PD trafficking, ise1 and ise2 mutants display increased proportions of twinned and branched PD compared with WT embryos (16)(17)(18); this increase is likely attributable to more de novo production of secondary PD. In support, reduction of ISE1 and/or ISE2 transcript levels in mature leaves by gene silencing causes specific increases in secondary PD concomitant with increased PD transport (18).…”
mentioning
confidence: 99%
“…ISE2 encodes a predicted DEVHtype RNA helicase (16), and microscopic examination of transgenic plants constitutively expressing ISE2 tagged at its C terminus with GFP (ISE2-GFP) suggested that ISE2-GFP localized to granules that were often associated with chloroplasts (figure 8A of ref. 16) or, less frequently, with a marker for plant RNA processing bodies, mRNA decapping enzyme 2 (DCP2)-RFP (figure 9 of ref. 16).…”
mentioning
confidence: 99%